Some confluences in the paths of Zambrano and Machado: philosophical poiesis - Sánchez Espillaque, Jessica (Anales del Seminario de Historia de la Filosofía, 2026)
In contrast to the rationalist conception that has sought to separate philosophy and poetry for centuries, María Zambrano’s approach, with her poetic reason, and its dawn in the thought of Antonio Machado, demonstrate the original conjunction between these two disciplines, revealing, in turn, the inexorable mutability and temporality of our existence. Therefore, this research analyzes the constant transit from philosophy to poetry and vice versa, which permeates the thinking of these two Andalusian thinkers, to highlight the points at which their paths intersect. An encounter that culminates in a revaluation of the poietic word (as a creativeword) as a means through which to understand man, and his reality, in all its integrity.
Keywords: path; poiesis; original word; time; shadow